State investment tax incentives: a zero-sum game? - Robert S. Chirinko; Daniel J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2007)
Though the U.S. federal investment tax credit (ITC) was permanently repealed in 1986, statelevel ITCs have proliferated over the last few decades. Are these tax incentives effective in increasing investment within the state? How much of this increase is due to investment drawn away from other states? Based on a panel dataset for all 50 states, we find a significant channel for state tax incentives on own-state economic activity and document the importance of interstate capital flows. Whether state investment incentives are a zero-sum game is less certain and depends on the definition of the set of competitive states.
Keywords: H71; H77; H25; H32; 330; Investitionspolitik; Steuerbegünstigung; USA